The subjective well-being status and influencing factors of Jiaying university undergraduates in the post covid-19 era - LIU, XIAOHONG; Fernando, Yudi (Journal of E-business and Management Science, 2023)
Subjective well-being is a key index to measure the quality of life of individuals and groups. university students' subjective well-being is a comprehensive reflection of their campus life quality and mental health level. The level of subjective well-being of university students directly affects the level of mental health. The purpose of this study is to investigate the subjective well-being of Chinese college students in the post-COVID-19 era, and what are the main factors affecting the subjective well-being of university students? In this study, face-to-face interviews were used to collect information and convenient sampling techniques were adopted. The results show that the subjective well-being index of university students in Hakka area of China is relatively low. The results show that the main factors affecting the subjective well-being of university students in China include academic stress, interpersonal stress, employment stress and financial stress. According to the above analysis results, the subjective well-being of undergraduates in the post-COVID-19 period is relatively low. Academic stress, employment stress, interpersonal stress and economic stress are the main factors that affect undergraduates' subjective well-being. In future research, we can use experimental and intervention research and other methods to conduct more in-depth research on subjective well-being. In addition, the student management departments of universities should pay more attention to the subjective well-being of undergraduates. Group training can be used to improve undergraduates' ability to resist stress, so as to enhance their subjective well-being.